Fi Zilal al-Qur’an about Dawlah Islamiyyah (Book Review) - Nur Yasin; Burhan Djamaluddin; Agus Aditoni (Alliance of Health Activists (AloHA), 2021)
Sayyid Qutb as a well-known thinker and one of the most influential figures in the 20th century. Dawlah islamiyyah has indeed become the ultimate goal for Sayyid Qutb by making Islam as the big umbrella in the form of a supranational state and hakimiyyah as its legal principle. However, Sayyid Qutb’s interpretation of dawlah islamiyyah has aspects of flexibility and tolerance that need to be considered. Some readers of the Fi Zilal al-Qur'a n exegesis - from among the radicals - saw Sayyid Qutb’s thoughts directly to the end of his idea and left the chronology of the stages of his thought, so that it became extreme. Keywords: Surah Al-Rahman; ‘Ali Al Shabuni; Shafwah Al-Tafasir; uniqueness; methodology; interpretation